THE USAGE OF VANDERVEKEN THEORY TO ANALYSE ILLOCUTIONARY ACTS ON THE “OPINION” COLUMN OF THE JAKARTA POST EDITION 1st - 5th of SEPTEMBER 2018 - Rani Herning Puspita; Sunarti Sunarti (JOALL (Journal of Applied Linguistics and Literature), 2019)
There are various columns in the newspaper, from the news columns to the opinion column. The speaker letter column contains letters from the speaker which contain various things such as opinions, responses, criticisms, aspirations, suggestions and complaints. Sometimes the language the speaker uses to convey his intent is not explicitly stated. The problems discussed in this study are any speech acts contained in the opinion column of the Jakarta Post newspaper. The objectives of this study are (1) What types of illocutionary speech acts used by speakers in the "Opinion" column in The Jakarta Post newspaper; (2) What functions of illocutionary speech acts used in the "Opinion" column in the Jakarta Post newspaper. The approach used in this study is descriptive qualitative. The method of data collection uses note and technique notes. The data population used in this study is the speech contained in the column "Opinion" in the August 2009 edition of the Jakarta Post newspaper. The results of this study are that every person has different ways in giving their opinion about news or topic. It can be complaining, agreeing, and request. Those all expressive can be analysed using illocutionary acts or speech acts.